THE COUNSELING AND TRAINING PROGRAM FOR TRADITIONAL CHICKEN FARMING OF KUB (KAMPUNG UNGGUL BALITBANGTAN) CHICKEN STRAIN AT TAFENA KUAN GROUP IN CAMPLONG II VILLAGE - Tri Utami; Maxs Urias Ebenheizer Sanam; Inggrid Trinidad Maha; Dewi F. L. Djungu (Universitas Nusa Cendana, 2021)
The counseling and training program for traditional chicken farming of KUB (Kampung Unggul Balitbangtan) chicken strain had been done at Tafena Kuan group in Camplong II Village. The purpose of implementing this program is community empowerment in developing local poultry farming businesses in order to overcome food insecurity, reduce dependency on imported poultry commodities, and build community independence in providing good quality protein sources of food. This program was carried out from April to December 2020 at Tafena Kuan group, located in Camplong II village, Kupang Regency of East Nusa Tenggara province. The Tafena Kuan group has 22 members of chicken farmers. The community service team provided assistance in the form of six KUB chickens, chicken feed, vaccines, vitamins, and worm medicine to each farmer. The counseling and training had been followed by all farmers. Farmers of the Tafena Kuan group built chicken cages independently using local materials and started running a KUB chicken breeding intensively.